2015
DOI: 10.1038/srep11448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of papain-based gel on type I collagen - spectroscopy applied for microstructural analysis

Abstract: Considering the improvement of biomaterials that facilitate atraumatic restorative techniques in dentistry, a papain-based gel can be used in the chemomechanical removal of decayed dental tissue. However, there is no information regarding the influence of this gel on the structure of sound collagen. The aim of the present study was to investigate the adsorption of a papain-based gel (PapacarieTM) to collagen and determine collagen integrity after treatment. A pilot study was first performed with 10 samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 23 publications
4
48
0
2
Order By: Relevance
“…The comparison of the FTIR spectra with Type I collagen (Sigma Aldrich, Merck KGaA, Darmstadt, Germany) revealed a substantial similitude in the peaks; finally the ratio of absorbance measured at 1235 cm −1 and 1450 cm −1 , which were all >0.9, suggests the presence of native collagen triple helix in all the samples [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of the FTIR spectra with Type I collagen (Sigma Aldrich, Merck KGaA, Darmstadt, Germany) revealed a substantial similitude in the peaks; finally the ratio of absorbance measured at 1235 cm −1 and 1450 cm −1 , which were all >0.9, suggests the presence of native collagen triple helix in all the samples [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The compositional analysis of all samples was performed using the Attenuated Total Reflectance technique of Fourier Transformed Infrared Spectroscopy (ATR-FTIR, Varian 610, Agilent Technologies, CA, USA), using a diamond crystal coupled to the spectrometer, as previously described by Júnior et al . 11 . The ATR-FTIR spectra of each sample were obtained at a resolution of 4.0 cm −1 , with 80 scans in the range of 4000 to 500 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…An in vitro study using the technique of attenuated total reflectance Fourier-transform infrared spectroscopy (ATR-FTIR) demonstrated that papain-gel did not lead to the degradation of collagen and this product could be safely used in minimally invasive dentistry. As the integrity of sound collagen is preserved after the application of the papain-based gel, this product is indicated for the selective removal of infected dentin, leaving the underlying affected dentin intact and capable of re-mineralization 11 . Papacárie gel underwent initial studies over the last ten years 12 in a children’s dental clinic.…”
mentioning
confidence: 99%
“…50% PEG400 in 0.5Macetic acid produced workable films with distinct banded structures, yielding Raman spectra typical of signature region of collagen type 1 7 . By changing the buffer to 50% PEG35000(300mg/ml in DH 2 O) 8 0.5Macetic acid, we first observed a dramatic increase in concentration.…”
Section: Raman Spectroscopy Of Naturally Aligning Filmsmentioning
confidence: 99%